New species of the Latithorax Species Group of Velarifictorus Randell, 1964 (Orthoptera: Gryllidae: Gryllinae) from China - Ma, Libin (Zootaxa, 2019)
The Latithorax Species Group of Velarifictorus contains a number of species that are small and possess a stick-shaped ectoparamere of the epiphallus. Here, three new taxa of this group from China are described and illustrated. These are: Velarifictorus agitatus shaanxiensis sp. and subsp. nov., V. a. yunnanensis subsp. nov., V. stultus sp. nov.